2012
DOI: 10.1186/1471-2164-13-10
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome changes during fruit development and ripening of sweet orange (Citrus sinensis)

Abstract: BackgroundThe transcriptome of the fruit pulp of the sweet orange variety Anliu (WT) and that of its red fleshed mutant Hong Anliu (MT) were compared to understand the dynamics and differential expression of genes expressed during fruit development and ripening.ResultsThe transcriptomes of WT and MT were sampled at four developmental stages using an Illumina sequencing platform. A total of 19,440 and 18,829 genes were detected in MT and WT, respectively. Hierarchical clustering analysis revealed 24 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 53 publications
(71 reference statements)
9
96
1
Order By: Relevance
“…The content of total sugar, fructose, glucose and sucrose showed a similar level among these cultivars. Also the similar content of total sugars were observed in other grapefruit and sweet lemons [24].…”
Section: Physicochemical Properties Of Pink Pomelo Juicessupporting
confidence: 83%
“…The content of total sugar, fructose, glucose and sucrose showed a similar level among these cultivars. Also the similar content of total sugars were observed in other grapefruit and sweet lemons [24].…”
Section: Physicochemical Properties Of Pink Pomelo Juicessupporting
confidence: 83%
“…Citrate Synthase (CS) has been reported to be the key enzyme for citric acid synthesis in citrus [16]. However, other research has found no relationship between CS activity and the citric acid level in citrus fruits [17]- [19]. In this investigation, the two CitCSs families increased expression as the time under water stress increased, and having the same trend with the fruit citric acid content.…”
Section: The Influence Of Water Stress On Citric Acid Metabolism Relamentioning
confidence: 56%
“…Studies employing citrus metabolomics have been focused on discovering nutritional biomarkers and the physiological and biochemical impacts of bud mutation (Rangasamy and Ratledge, 2000;Heinzmann et al, 2010). Comprehensive transcript profiling studies have been widely applied in sweet orange Xu et al, 2009;Yu et al, 2012), lemon (Chypre et al, 2012), mandarin (Cercos et al, 2006) and pummelo (Zheng et al, 2012). Combined high-throughput technologies have also been widely used for citrus research (Kerr and Huber, 1987;Katz et al, 2011;Yun et al, 2012) in recent years.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%